POETIC MODERNITY ESTABLISHED IN ADONIS' CRITICAL PROJECT: A CRITICAL ANALYTICAL APPROACH - Adel Najeh Abbas AL-Fatlawi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The basic principles that guide the paths of this research in its approach to the exclusion and contents of establishing the poetic modernity of Adonis in terms of its conditions and foundations, and the possibility of its realization in the modern and contemporary Arab cultural scene... are based on several data and methodological premises, the most important of which is that the hypothesis of this study is based on non-separation Among the awareness of the dimensions of poetic modernity among Adonis, and between his project of reading Arab ancient, modern and contemporary thought, the other premise is that Adonis bet on the possibility of achieving contemporary Arab poetic modernity is because of his belief that the faces and manifestations of this modernity are authentic in our Arab history in general and history For the creativity of ancient poetry in particular, and that is why Adonis - and contrary to many studies that distorted and misread his concept of modernity in his critical project. was and if he relied on Western" references and components for his belief in intellectual, global and cosmic, he was a proponent of establishing Arab poetic modernity with origins. Heritage ,so in such a case it will be an extension of it, meaning that Adonis did not fall into westernization, and cultural dependency on the West, and did not occur at the same time in the veneration tendency of the past of Arab heritage and thought, but rather tried to establish a vision of poetic modernity that does not stop with the gains of Western modernity with its creative dimension from On the one hand, and not in the same Guest cut off the roots of their properties and their tributaries in Arabic and its components on the other.